A Time-Frequency Acoustic Emission-Based Technique to Assess Workpiece Surface Quality in Ceramic Grinding with PZT Transducer - Aulestia Viera, Martin A.; Aguiar, Paulo R.; Oliveira Junior, Pedro; Alexandre, Felipe A.; Lopes, Wenderson N.; Bianchi, Eduardo C.; da Silva, Rosemar Batista; D'addona, Doriana; Andreoli, Andre (MDPI, 2019)
Innovative monitoring systems based on sensor signals have emerged in recent years in view of their potential for diagnosing machining process conditions. In this context, preliminary applications of fast-response and low-cost piezoelectric diaphragms (PZT) have recently emerged in the grinding monitoring field. However, there is a lack of application regarding the grinding of ceramic materials. Thus, this work presents an analysis of the feasibility of using the acoustic emission signals obtained through the PZT diaphragm, together with digital signal processing in the time-frequency domain, in the monitoring of the surface quality of ceramic components during the surface grinding process. For comparative purpose, an acoustic emission (AE) sensor, commonly used in industry, was used as a baseline. The results obtained by the PZT diaphragm were similar to the results obtained using the AE sensor. The time-frequency analysis allowed to identify irregularities throughout the monitored process.
Keywords: acoustic emission; ceramic grinding; digital signal processing; piezoelectric transducer; sensor monitoring; short-time Fourier transform